Study of pseudo soldering based on eddy current pulsed thermography - Zhou, Xiuyun; Xue, Yun; Chen, Yaqiu; Lu, Xiaochuan; Liu, Zhen (Applied physics letters, 2017)
Pseudo soldering defects can break the electrical and mechanical connection between components and the print circuit board and eventually cause failure of the whole electronic equipment. In this letter, the eddy current pulsed thermography (ECPT) method was used for defect inspection of small-sized solder joints. The identification of defects of solder joints is based on the heat transfer between various component structures. The experimental results indicated that the ECPT method can be effectively used for defect detection and location of the solder joints. In addition, it can distinguish different degrees of pseudo soldering.